(untitled) - Andreasen, J O (Copenhagen, Denmark, 1994)
this classic text encompasses the full scope of acute dental trauma, including all aspects of surgical, endodontic, orthodontic, pedodontic and prosthodontic therapy after injury. This edition updates trauma therapy in light of the diagnostic and therapeutic advances made in recent years. New chapters have been added including wound healing and the long-term prognosis of various trauma entities, analysed in co-operation with the Statistical Research Unit of the University of Copenhagen. There are also new procedures for the treatment of anterior tooth loss following trauma, including auto-transplantation of teeth, resin-retained bridges, the use of implants, and reconstruction of lost tissue in the anterior region
Keywords: Dental surveys,Tooth Injuries,Dentistry; Aesthetics